2005
DOI: 10.1111/j.1464-410x.2005.05641.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tolterodine as a first‐line treatment for non‐neurogenic voiding dysfunction in children

Abstract: OBJECTIVE To assess the effect of antimuscarinic treatment with tolterodine combined with behavioural modification as a first‐line treatment, before invasive investigation, in children with non‐neurogenic voiding dysfunction but no obvious anatomical or neurogenic cause. PATIENTS AND METHODS The study comprised 44 children presenting with voiding dysfunction (30 girls and 14 boys, mean age 7 years, range 5–14); all had a noninvasive evaluation consisting of a history, urine analysis, renal and bladder ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Relevant epidemiological studies allow for the supposition that the prevalence of LUTD in children is variable, possibly affecting between 2% and 25% of the population [3][4][5][6][7][8][9][10][11][12]. Despite this disparity in the prevalence reported in studies, in which the informants are generally the parents, LUTD is common in the pediatric population and represents a challenge for specialized interdisciplinary teams.…”
Section: Introductionmentioning
confidence: 89%
“…Relevant epidemiological studies allow for the supposition that the prevalence of LUTD in children is variable, possibly affecting between 2% and 25% of the population [3][4][5][6][7][8][9][10][11][12]. Despite this disparity in the prevalence reported in studies, in which the informants are generally the parents, LUTD is common in the pediatric population and represents a challenge for specialized interdisciplinary teams.…”
Section: Introductionmentioning
confidence: 89%
“…Randomized controlled trials evaluating efficacy of anticholinergics as primary treatment in addition to BM have demonstrated improved subjective and objective outcomes [14,15]. Most subjects included in these studies had low post-void residuals, something that was found in less than 20% of our cohort.…”
Section: Discussionmentioning
confidence: 93%
“…Lately, it has been reported that tolterodine tartrate which has a similar effect and less side effects than oxybutynin, should be used instead of this drug [14,20,22,[24][25][26] . In our study, tolerated side effects were seen in 10 patients, and the drug was found to be safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a recent concept is that the efficacy of treatment might be determined by clinical symptoms of patients. The touchstone of this idea is based on the first study performed by Farhat et al [12] about dysfunctional voiding symptom score and other subsequent studies [13,14] . Recently, another new dysfunctional voiding and incontinence scoring system (DVAISS) with a different questionnaire and scoring system has been developed by Akbal et al [15] , but its efficacy is not supported by clinical studies in the literature.…”
Section: Introductionmentioning
confidence: 99%